Dependence of vehicle collisions with roe deer on spatial and temporal factors in Lithuania - Galinskaitė, Lina; Ignatavičius, Gytautas; Valskys, Vaidotas (International Conference “Environmental Engineering”, 2020)
Rising road densities, vehicle speeds limits and traffic volumes, combined with recent growth in the population density of various deer species, have increased the risk of DVCs across the world, causing a great deal of animal suffering, traffic safety problems and socio-economic costs. Object of this investigation was to find out collisions trend with roe deer (Capreolus capreolus) in Lithuania. The aim of our study was to determine where in Lithuania accidents occure more frequently and evaluate these accidents in time. In 2013–2017 number of AVCs in Lithuania was recorded more then 12 011 times, over half of 7155 occur with roe deer. The temporality of accidents was studied under three scales – daily, weekly and seasonal. Daily peaks start at 7:00 (8.75%), 8:00 (6.08%). Evening peaks, start at 17:00 (7.71%), other at 22:00 (10.64%) hours. Week collisions with roe deer increase on Friday 14.9%. The risk of collision with roe deer varies over the year – the majority of crashes occur in May 14.7% and November 10.7%. In spatial study localization of collision data with ArcGIS 10.3. It was found that road surrounding landscape dominated by agricultural land collisions occurred at a maximum of 29.77%. 19.10% collisions were recorded in the forest area. In built-up areas 11.85%. Analysis of these trends allow to simulate and predict when and where the highest risk of DVCs occurs. In conclusion, this could give valuable information and constitute a manageable tool for the road managers, planners, scientist, wildlife conservationist who are interested in these type of accidents in regions of Lithuania.